Characterization of Ganoderma pseudoferreum mitogenome revealed a remarkable evolution in genome size and composition of protein-coding genes - Lu, Jinpeng; Qin, Chunxiu; Huo, Siyan; Wang, Huanwei; Norvienyeku, Justice; Miao, Weiguo; Liu, Wenbo (Frontiers in Plant Science, 2025)
Red root disease in rubber trees, caused by Ganoderma pseudoferreum, is a prevalent and severe soil-borne disease in rubber tree cultivation areas. The pathogen exhibits complex infections, with multiple transmission pathways, making the disease highly concealed and difficult to diagnose in its early stages. As a result, prevention and control are challenging, posing a serious threat to rubber production. Currently, the relevant information, evolutionary trajectory, and sequence divergence of the mitochondrial genome of G. pseudoferreum remain unknown. Here, we assembled the complete mitochondrial genome of G. pseudoferreum,which is 40, 719 bp long and contains 14 protein-coding genes (PCGs), genes encoding small and large ribosomal subunits, 22 mitochondrial-encoded tRNAs, and four hypothetical proteins. The genomic content and characteristics, along with IPS mapping analysis and phylogenetic analysis, reveal a significant similarity between G. pseudoferreum and G. lingzhi. The results of RNA editing site analysis, codon usage bias and evolutionary pressure analysis reveal that during environmental adaptation, species of Ganoderma may alter certain key PCGs to adopt distinct evolutionary trajectories, differentiating themselves from other fungi in Basidiomycota, while leaving evolutionary traces. Our study provides new insights into the evolutionary direction and pattern of G. pseudoferreum and Ganoderma by exploring the evolutionary trajectory of mitochondrial genomes of G. pseudoferreum and Ganoderma.